Timeline of hypoglossal motor neuron death and intrinsic tongue muscle denervation in high-copy number SOD1G93A mice - Fogarty, Matthew J.; Drieberg-Thompson, Joy R.; Bellingham, Mark C.; Noakes, Peter G. (Frontiers in Neurology, 2024)
In amyotrophic lateral sclerosis (ALS) postmortem tissue and the SOD1 mouse model at mid-disease, death of hypoglossal motor neurons (XII MNs) is evident. These XII MNs innervate the intrinsic and extrinsic tongue muscles, and despite their importance in many oral and lingual motor behaviours that are affected by ALS (e.g., swallowing, speech, and respiratory functions), little is known about the timing and extent of tongue muscle denervation. Here in the well-characterised SOD1G93A (high-copy) mouse model, we evaluated XII MN numbers and intrinsic tongue muscle innervation using standard histopathological approaches, which included stereological evaluation of Nissl-stained brainstem, and the presynaptic and postsynaptic evaluation of neuromuscular junctions (NMJs), using synapsin, neurofilament, and α-bungarotoxin immunolabelling, at presymptomatic, onset, mid-disease, and endstage timepoints. We found that reduction in XII MN size at onset preceded reduced XII MN survival, while the denervation of tongue muscle did not appear until the endstage. Our study suggests that denervation-induced weakness may not be the most pertinent feature of orolingual deficits in ALS. Efforts to preserve oral and respiratory functions of XII MNs are incredibly important if we are to influence patient outcomes.